1999
DOI: 10.1016/s0926-6410(98)00032-9
|View full text |Cite
|
Sign up to set email alerts
|

Cortical processing of complex tone stimuli: mismatch negativity at the end of a period of rapid pitch modulation

Abstract: In this study, synthesised instrumental tones were used to examine human auditory cortical processes engaged at the end of a period of w rapid pitch modulation. It was previously S.J. Jones, O. Longe, M. Vaz Pato, Auditory evoked potentials to abrupt pitch and timbre Ž . x change of complex tones: electrophysiological evidence of 'streaming'?, Electroencephalogr. Clin. Neurophysiol., 108 1998 131-142 suggested that the 'change-N1' produced by infrequent changes in pitch or timbre of a continuous complex tone r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 53 publications
(6 reference statements)
3
16
0
Order By: Relevance
“…As in the previous study (Vaz Pato and Jones, 1999), the MN1 and MP2 at the end of the period of pitch oscillation appeared to be more anteriorly distributed on the scalp than the CP1, CN1 and CP2 at the beginning of the oscillatory period. Whereas the CN1 was of comparable amplitude at Fz and Cz, MN1 was more evidently larger at Fz for all stimulus durations except the shortest (Fig.…”
Section: Scalp Distribution Of P1 N1 and P2 Potentialssupporting
confidence: 79%
See 2 more Smart Citations
“…As in the previous study (Vaz Pato and Jones, 1999), the MN1 and MP2 at the end of the period of pitch oscillation appeared to be more anteriorly distributed on the scalp than the CP1, CN1 and CP2 at the beginning of the oscillatory period. Whereas the CN1 was of comparable amplitude at Fz and Cz, MN1 was more evidently larger at Fz for all stimulus durations except the shortest (Fig.…”
Section: Scalp Distribution Of P1 N1 and P2 Potentialssupporting
confidence: 79%
“…When pitch changes are made at rates greater than about 10/s the associated N1 and P2 potentials are markedly attenuated or absent, but on resumption of a steady pitch a large (up to 10 mV) negative potential with a more anterior distribution is evoked (Vaz Pato and Jones, 1999). We have argued that this is probably an MMN in a relatively pure form, undistorted by overlapping N1 components.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…The results indicated that the primary auditory cortex responds immediately to stimulus changes and integrates stimulus features over a period of about 200 ms. In another series of studies on fusion of rapid stimulus alternations (Vaz Pato and Jones, 1999;Jones et al, 2000a,b), continuous synthesized musical instrument notes oscillated between two pitches at a rapid rate (8-16 notes/s, i.e., every 63-125 ms) and the 'changetype' N 1 and P 2 potentials associated with each individual change were abolished ('fused oscillations'), indicating an integration time of around 100 ms. Thus, different approaches to determine the time span of stimulus constancy or temporal integration resulted in quite different results (between 30 and 300 ms), depending on possible confounding factors such as spectral changes, adaptation rates, refractory periods and on/off effects.…”
Section: N-complex and Acoustic Changementioning
confidence: 99%
“…Previous studies on temporal integration, change and constancy (Alain et al, 1997;Vaz Pato and Jones, 1999;Jones et al, 2000a,b;Gage and Roberts, 2000;Roß et al, 2002;Alain et al, 2004;Heinrich et al, 2004) used stimuli that included spectral changes due to stimulus onset and offset that may have interacted with duration. Consequently, depending on the procedures employed, different values ranging between 30 and 300 ms were obtained.…”
Section: The N-complex and The Limits Of Constancymentioning
confidence: 99%